BRAINSTORMING BUSINESS MODEL CANVAS PADA FORMULASI STRATEGI “RABUK DIYANG” SEBAGAI PRODUK KHAS KABUPATEN INDRAGIRI HILIR - Roberta Zulfhi Surya; Rosliana Rosliana (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2020)
This research uses integrating brainstorming method and Business Model Canvas, model is done with brainstorming method. The Canvas Business Model covers nine blocks, Customer Relationships, Key Partners, Value Propositions, Customer Segments, and cash flow, key resources (key resources), key activities (key activities) and cost structures (cost structures). The result of the research shows strategy with Business Model Canvas can effectively and efficiently in determining Rabuk Diang Empowerment Group strategy